Physical recreation as working method of social prophylaxis - Łukowski, Karol (Contemporary problems of physical and health culture, 2022)
In response to emerging threats and social dysfunctions, different ways of preventive work are practised, aiming at promoting pro-health attitudes and shaping positive reinforcements. The presented research describes streetworking activities, in which the main role is played by physical recreation as a method of preventive and therapeutic work with children, youth and their parents. The research was conducted using the Evidence-Based Practice method. The main aim of the article is to present participantsʼ opinions and observational evidence through diagnosis and evaluation, aimed at achieving social benefits and assessing effectiveness during the activities. Prevention activities aim to prevent and reduce the risk of adverse environmental phenomena. Therefore, in order to examine the results of activities, it is necessary to take into account the motivation of the pupils to take up physical activity, strengthening their predispositions to act and building positive relationships in the group.